2011
DOI: 10.4028/www.scientific.net/amr.332-334.41
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Laminated Veneer Lumber with Ramie Fibre

Abstract: This paper describes a preliminary investigation on the use of ramie fibre/ phenol formaldehyde (PF) composite to reinforce laminated veneer lumber (LVL). This research was conducted in two phases. Phase 1 the ramie fibre was treated with KH-550 silane coupling agent. Phase 2 different numbers of sheets ramie fibre/PF were added in different location of LVL to reinforce. The reinforced LVL was hot pressed at one time. A control group of unreinforced LVL was also manufactured. The results showed that the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The study found that making use of woven glass fiber to reinforce LVL had some positive influences and some negative influences on the mechanical properties. Wang et al (2011) introduced an investigation to reinforce LVL with ramie fiber. The study indicated that using ramie fiber to enhance LVL could improve the mechanical properties of LVL, especially the level of shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that making use of woven glass fiber to reinforce LVL had some positive influences and some negative influences on the mechanical properties. Wang et al (2011) introduced an investigation to reinforce LVL with ramie fiber. The study indicated that using ramie fiber to enhance LVL could improve the mechanical properties of LVL, especially the level of shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the related research, the effects of different forming structures and percentages of adding woven glass fiber on reinforced laminated veneer lumber were explored, which showed that the glass fiber has great effects on mechanical properties of laminated veneer lumber when reinforce by using woven glass fiber [7]. Glass fiber was also applied to reinforce the laminated veneer lumber, it greatly improved the properties of laminated veneer lumber, especially the shear strength [8,9]. Meanwhile, it was found that the polypropylene material when reinforced by fiber has greater flexural strength and lower water absorption rates [10].…”
Section: Introductionmentioning
confidence: 99%
“…The research indicated that using woven glass fiber to reinforce the LVL had both positive and negative effects on mechanical properties of LVL. Wang et al (2011) tried to enhance LVL by adding ramie glass fiber. The study showed that the ramie fiber had a positive influence on the mechanical properties; in addition, the shear strength had an especially great improvement.…”
Section: Introductionmentioning
confidence: 99%